Simultaneous Spectrophotometric Determination of Paracetamol and p-Aminophenol by H-point Standard Addition Method and Partial Least Squares Regression - KARIMI, M.A.; NATEGHI, M.R.; MALEKZADEH, M.; BANIFATEMEH, F.; MORADLOU, O. (Asian Journal of Chemistry, 2010)
Two new, simple, inexpensive and sensitive methods for the simultaneous spectrophotometric determination of paracetamol (PAR) and p-aminophenol (PAP) by H-point standard addition method (HPSAM) and partial least squares (PLS) calibration is described. The methods were based on the difference in the rate of reduction of iron(III) with PAR and PAP in the presence of 2,2'-bipyridine (Bpy) and subsequent complex formation between resulted Fe(II) and 2,2'-bipyridine. The coloured complex of [Fe(Bpy)3]2+ resulted can be monitored at 520 nm. The results showed that the simultaneous determination of PAR and PAP could be performed in their concentration ranges of 0.4-70.0 and 0.03-8.0 μg mL-1 for HPASM, 2.0-100.0 and 0.2-10.0 μg mL-1 for PLS method, respectively. The total relative standard error for applying the PLS method on 10 synthetic samples in the concentration ranges of 4.0-28.0 μg mL-1 of PAR and 0.5-6.0 μg mL-1 of PAP was 3.79. The proposed methods were successfully applied to the simultaneous determination of PAR and PAP in several commercially available PAR formulations and satisfactory results were obtained.